2019
DOI: 10.1111/ped.13907
|View full text |Cite
|
Sign up to set email alerts
|

Accurate detection of renal leukemic involvement in children using 3‐D computed tomography modeling

Abstract: Background The rate of renal involvement in pediatric acute lymphoblastic leukemia (ALL) at diagnosis varies between reports because renal involvement is diagnosed on renal size larger than aged‐matched standards on conventional modalities. We propose a new method for precise renal involvement detection using 3‐D enhanced computed tomography (CT) reconstruction. Methods Twenty‐five children with ALL were evaluated utilizing 3‐D enhanced CT reconstruction to measure renal volume before and after induction thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In addition to this, different screening modalities such as intravenous pyelogram, ultrasound, and computerized tomography have been preferred in those. [ 4 , 9 , 14 ] The above circumstances might cause inadequate estimation of the frequency of renal abnormalities in ALL patients. Most commonly reported renal imaging abnormalities are bilateral, diffuse enlargement of kidneys, and/or hyperechoic pattern, and these findings have been accepted as a sign of renal leukemic involvement in the previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to this, different screening modalities such as intravenous pyelogram, ultrasound, and computerized tomography have been preferred in those. [ 4 , 9 , 14 ] The above circumstances might cause inadequate estimation of the frequency of renal abnormalities in ALL patients. Most commonly reported renal imaging abnormalities are bilateral, diffuse enlargement of kidneys, and/or hyperechoic pattern, and these findings have been accepted as a sign of renal leukemic involvement in the previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…D’Angelo et al [ 10 ] demonstrated that prognosis of patients with NM at the time of diagnosis was worse with respect to the patients without NM. Neglia et al, Fujiki et al, and Taylor et al [ 5 , 8 , 14 ] did not consider NM as having an impact on prognosis in comparison to the presence of other well-defined prognostic criteria. Hann et al [ 4 ] showed that the NM was associated with worse survival in cases with better risk factors defined at the era of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation